Beyond Implementation: Sustaining Family-Centered Rounds. Issue 3 (May 2015) - Nichols, Kara; Crow, Karen; Balakas, Karen
Abstract : Abstract: Family-centered care encourages patients and families to participate in the planning and delivery of care based on personal preferences and individual needs. For pediatric patients and families, family-centered rounds (FCRs) represent a standard of care that involves patients and families partnering with the healthcare team to share information and make decisions about care. Our healthcare team strongly believes that FCRs are critical to providing excellence in care. Our initial attempt to implement and then sustain FCRs presented challenges that required changing the culture to one that consistently partners with patients and families and appreciates the role they play in the care of their children. Incorporation of observations and feedback from family advisors, a consistent process for rounding, and education for team members about expectations for participation were needed to revive and sustain FCRs. Through continued evaluation and collaboration, our unit worked to establish a standard approach to FCRs that benefits the patient and family as well as to the healthcare team. Abstract : Family-centered rounds enhance communication between members of the healthcare team and the patient and family, however there can be significant barriers to making this happen consistently. Nurses in this pediatric unit share their experiences with family-centered rounds and their eventual success in incorporating them into daily care.